Maïssa Bey’s Au commencement était la mer… and Hizya: toward a ‘writing of erosion’ - HAMDI, Houda (Journal of Human Sciences, 2022)
Maïssa Bey’s novels often hold confusing and sad closures that leave the reader with a sense of puzzlement and bitterness. As the stories in Au commencement était la mer… and Hizya unfold, the reader becomes the witness of the life of young women who go through a variety of experiences and hardships that leave little room for personal fulfillment. The falling apart environment, which is also reflected in the setting’s description, becomes to a large extent a reflection of the protagonists’ inner self. The author’s aesthetic choices further reinforce this dominating atmosphere. The present paper contends that the sense of bitterness and collapse, the heroines’ turmoil, the setting’s description, and the elaborated scripture where typography, division, and structure interplay, contribute in creating what I would like to call a ‘writing of erosion’; a writing that voices the daily tragedies of marginalized young generations with stifled voices and crushed dreams.